Keluarga Spiritual Yang Melampaui Fisik: Doktrin Adopsi Dan Implikasinya Bagi Gereja Di Indonesia - Bima Anugerah (Sekolah Tinggi Teologi Kharisma, 2023)
AbstractIndonesia is a pronatalist country that gives high priority to marriage and the presence of children in the family. However, it must be acknowledged that there are families who cannot have children (barren). In addition, there are also people who are not married. In the church, these people have a place because they are children in God's family. The concept of God's family providing this kind of acceptance is based on the doctrine of adoption. The doctrine of adoption states that a person who believes in Christ is a person who is justified and regenerated so that he is adopted as a child in God's family. Through the church, those who are barren and unmarried get a new family that is not bound by physical relationships. This truth offers an alternative narrative compared to the pronatalist narrative that exists in Indonesian society. Through the concept of the church as God's family, which is based on the doctrine of adoption, those who are barren and unmarried gain a place in the church as members of God's family. AbstrakIndonesia adalah negara pronatalis yang memberi prioritas tinggi terhadap pernikahan dan kehadiran anak di dalam keluarga. Namun, perlu diakui bahwa ada keluarga yang tidak memiliki keturunan. Selain itu, ada juga orang-orang yang tidak menikah. Di dalam gereja, orang-orang ini mendapatkan tempat merupakan anak di dalam keluarga Allah. Konsep keluarga Allah yang memberikan penerimaan seperti ini didasarkan pada doktrin adopsi. Doktrin adopsi menyatakan bahwa orang yang beriman kepada Kristus adalah orang yang dibenarkan dan dilahirbarukan sehingga diangkat menjadi anak di dalam keluarga Allah. Melalui gereja, yang tidak memiliki keturunan dan selibat mendapatkan keluarga baru yang tidak terikat oleh hubungan lahiriah. Kebenaran ini menawarkan sebuah narasi alternatif dibandingkan narasi pronatalis yang ada di masyarakat Indonesia. Melalui konsep gereja sebagai keluarga Allah, yang didasarkan pada doktrin adopsi, yang tidak memiliki keturunan dan selibat mendapatkan tempat di dalam gereja sebagai anggota keluarga Allah.